Does saffron supplementation have favorable effects on liver function indicators? A systematic review and meta-analysis of randomized controlled trials. Issue 23 (15th August 2022) - Mousavi, Seyed Mohammad; Mokhtari, Pari; Asbaghi, Omid; Rigi, Somaye; Persad, Emma; Jayedi, Ahmad; Rezvani, Hamid; Mahamat-Saleh, Yahya; Sadeghi, Omid
Abstract: Several pharmaceutical and non-pharmaceutical approaches have been suggested to improve liver health. There is a large discrepancy in the effects of saffron supplementation on liver function in adults. To fill this knowledge gap, this systematic review and meta-analysis of randomized controlled trials (RCTs) assess the effects of saffron supplementation on liver enzymes alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphatase (ALP). A systematic search current to August 2020 was performed in PubMed/Medline, Scopus, Web of Science, and Google Scholar using relevant keywords to detect eligible articles. A random-effects model was used to estimate the weighted mean difference (WMD) and 95% confidence (95% CI). Nine eligible trials were included in the final analysis. The pooled analysis revealed that serum ALT concentrations were significantly reduced using saffron compared to placebo (WMD: −2.39 U/L; 95% CI: −4.57 to −0.22; P  = 0.03, I 2 = 87.9%, P  < 0.001). However, saffron supplementation did not affect levels of serum AST (WMD: 1.12 U/L; 95% CI: −1.42 to 3.65; P  = 0.39) or ALP (WMD: 4.32 U/L; 95% CI: −6.91 to 15.54; P  = 0.78). In the dose-response analysis, we did not find a significant dose-response relationship between dosage and duration of saffron supplementation on serum levels of ALT, AST, and ALP. We found that saffron supplementation can reduce ALT serum concentrations without significant effects on other liver function indicators, including AST and ALP. Nevertheless, future large RCTs on diverse populations are needed to understand better the effects of saffron and its constituents on these enzymes.